Representation of the Spatial Motion in the Malay language Based on the Conceptual Structure Theory: (Representasi Argumen Gerak Ruang Bahasa Melayu Berdasarkan Teori Struktur Konseptual) (Jurnal Bahasa, 2020)
Motion is understood as a change from one location to another. Therefore, this study focuses on spatial motion consisting of directional, extensional, state and causative motion. This study utilizes data from the Pangkalan Data Korpus Dewan Bahasa dan Pustaka database in Malaysia for its study samples. The analysis employs Jackendoff's (1997 & 2011) Theory of Conceptual Structure for its framework. The mapping of these arguments comprises three main stages, namely mapping to conceptual structure representation, mapping to conceptual tree diagrams and mapping to thematic roles. The results show that spatial motion is present in the [Event] and [States] functions that carry the basic formula [[[MOTION [x [Event] [Object] [Path] [Place]]]. The findings show that the lexical items balik, berlari, tinggal, terletak, berada, bunuh, paksa, benar and tolong have their own representation of arguments involving constituents such as [Event], [States], [Object] [Path] [Place] [Event] REASON], [NO Causative], [TRUE Causative] and [HELP Causative]. For the mapping stage in the thematic role, the item involved is the role of Actor, Theme, Goal, Source, Agent and Beneficiary (-). Accordingly, this study shows an adequate systematic representation of the conceptual structure, particularly in the spatial motion domain in the Malay language.Keywords: spatial motion, constituents, argument, conceptual structure and thematic